Αmbrakia as a contested space: Federal claims to power and the border management of a city-state in the second century BC - Scharff, Sebastian (Classica et Mediaevalia, 2025)
Situated in the border area of several powerful neighbors, the polis territory of Ambrakia was exposed to numerous territorial claims from its early history onwards. A close reading of the story of the quarrel of the gods fighting over the possession of the city reveals that the passage must be understood as an illustration of those various interests in the city prior to the Roman conquest. Yet it was precisely when the domination of Greek states in the region came to an end that the Ambrakiots undertook a remarkable border-management initiative including at least three boundary regulations dating to the 160s BC. This article asks for the reasons behind this initiative and emphasizes the political room for maneuver the Ambrakiots exploited after the Third Makedonian War.